CLE Peptide Signaling and Crosstalk with Phytohormones and Environmental Stimuli - Wang, Guodong; Zhang, Guohua; Wu, Mengyao (Frontiers in Plant Science, 2016)
The CLE (CLAVATA3/Endosperm surrounding region-related) peptide family is one of the best-studied secreted peptide families in plants. Accumulated data have revealed that CLE genes play vital roles on stem cell homeostasis in different types of meristems. Additionally, CLE genes have been found to perform various biological roles in plant growth and development, and in response to environmental stimuli. With recent advances on our understanding of CLE peptide function, it is showing that the existence of potential crosstalks of CLE peptides with phytohormones and external stimuli. Complex interactions exist in which CLE petides coordinate with hormones to regulate plant growth and development, and in response to external stimuli. In this article, we present recent advances in cell-cell communication that is mediated by CLE peptides combining with phytohormones and external stimuli, and suggest additional Arabidopsis CLE genes that are likely to be controlled by hormones and environmental cues.